Recurrent mutations drive rapid HIV escape from two broadly neutralizing antibodies in vivo - Elena V. Romero; Abigail E. Clyde; Elena E. Giorgi; Dylan H. Westfall; Walker Azam; Megan L. Taylor; Marina Caskey; Alison F. Feder; Lillian B. Cohn (Proceedings of the National Academy of Sciences, 2026)
Broadly neutralizing antibodies (bNAbs) show promise for HIV treatment and prevention, but are vulnerable to resistance evolution. Comprehensively understanding in vivo viral escape from individual bNAbs is necessary to design bNAb combinations that will provide durable responses. We characterize viral escape from two such bNAbs, 10-1074 and 3BNC117, using deep, longitudinal sequencing of full-length HIV envelope ( env ) genes from study participants treated with bNAb monotherapy. Improved sequencing depth and computational evolutionary analyses permit us to identify in vivo routes and parallelism underlying HIV escape from each bNAb, providing insight into this evolutionary process. We find that 10-1074 escape is restricted to a small number of previously documented pathways seen across participants, but these escape mutations 1) emerge via extensively recurrent mutation, 2) are not equally preferred, and 3) can preexist at low frequency in intrahost viral populations before therapy, although their detection does not predict rebound timing. In contrast, 3BNC117 escape follows background-specific patterns in which specific escape mutations present in one intrahost population rarely emerge or spread in other populations, except among highly related viruses. Despite this, 3BNC117 escape mutations can still emerge recurrently within their host. Our findings map longitudinal in vivo antibody escape across 20 diverse clade B HIV intrahost populations and reveal clinically relevant resistance dynamics that highlight how combination bNAb therapies will need to contend with extensively recurring escape mutations and dependence on genetic background.